Monitoring of biological markers indicative of doping: the athlete biological passport - Saugy, M.; Lundby, C.; Robinson, N. (British Journal of Sports Medicine, 2014)
The athlete biological passport (ABP) was recently implemented in anti-doping work and is based on the individual and longitudinal monitoring of haematological or urine markers. These may be influenced by illicit procedures performed by some athletes with the intent to improve exercise performance. Hence the ABP is a valuable tool in the fight against doping. Actually, the passport has been defined as an individual and longitudinal observation of markers. These markers need to belong to the biological cascade influenced by the application of forbidden hormones or more generally, affected by biological manipulations which can improve the performance of the athlete. So far, the haematological and steroid profile modules of the ABP have been implemented in major sport organisations, and a further module is under development. The individual and longitudinal monitoring of some blood and urine markers are of interest, because the intraindividual variability is lower than the corresponding interindividual variability. Among the key prerequisites for the implementation of the ABP is its prospect to resist to the legal and scientific challenges. The ABP should be implemented in the most transparent way and with the necessary independence between planning, interpretation and result management of the passport. To ensure this, the Athlete Passport Management Unit (APMU) was developed and the WADA implemented different technical documents associated to the passport. This was carried out to ensure the correct implementation of a profile which can also stand the challenge of any scientific or legal criticism. This goal can be reached only by following strictly important steps in the chain of production of the results and in the management of the interpretation of the passport. Various technical documents have been then associated to the guidelines which correspond to the requirements for passport operation. The ABP has been completed very recently by the steroid profile module. As for the haematological module, individual and longitudinal monitoring have been applied and the interpretation cascade is also managed by a specific APMU in a similar way as applied in the haematological module. Thus, after exclusion of any possible pathology, specific variation from the individual norms will be then considered as a potential misuse of hormones or other modulators to enhance performance.